Arylene–hexaynylene and –octaynylene macrocycles: extending the polyyne chains drives self-association by enhanced dispersion force. Issue 5 (23rd December 2020) - Kato, Shin-ichiro; Kumagai, Ryo; Abe, Tsukasa; Higuchi, Chisa; Shiota, Yoshihito; Yoshizawa, Kazunari; Takahashi, Nobutaka; Yamamoto, Koji; Hossain, Md Zakir; Hayashi, Kazuhiro; Hirose, Takashi; Nakamura, Yosuke
Abstract : We synthesized arylene–alkynylene macrocycles containing hexayne and octayne, which enables quantitative analysis of self-association constants depending on the length of the polyyne chains for the first time. Abstract : Tetraalkoxyphenanthrylene–hexaynylene and –octaynylene macrocycles, which represent the first examples of isolable arylene–alkynylene macrocycles (AAMs) that contain polyyne chains longer than tetrayne, were synthesized and their self-association behavior was examined. Extending the polyyne chain from diyne to tetrayne, hexayne, and octayne exponentially increased the self-association constant of the macrocycles.